Who Let the Dogs in? Antiblackness, Social Exclusion, and the Question of Who Is Human. (May 2019) - Parker, Lynette
This article illuminates how the lived experiences of Black men in comparison to experiences of dogs in society highlight antiblackness as the prevailing sentiment in America. This juxtaposition illuminates the psychological project embedded within antiblackness—to dehumanize Black people by elevating dogs alongside other racial groups that have been deemed as human. The article demonstrates how dogs have not only been embraced by Whites, but have been given access into spaces and granted civil liberties for which Blacks continue to struggle. The article looks at the role of dogs in a country that once categorized them as nuisances and marked them with distain by identifying them along with Blacks, Mexicans, Jews, Irish, Chinese, and Japanese as the "undesirable" elements of society. Today's acceptance of and advocacy for dogs as a social phenomenon demonstrates the possibility of an ideology shift by Whites, while simultaneously demonstrating their dogged determination to hold to an ideology that cast Black people as less than human.